2019
DOI: 10.1155/2019/9871424
|View full text |Cite
|
Sign up to set email alerts
|

Energy Evolution and Mechanical Features of Granite Subjected to Triaxial Loading‐Unloading Cycles

Abstract: Energy evolution varies during the whole process of rock deformation, and mechanical parameters are markedly altered under cyclic loading and unloading. In order to investigate the effects of confining pressure on energy evolution and mechanical parameters, cyclic loading and unloading experiments were performed for granite under six different confining pressures. The experiment revealed the confining pressure effect on variation and allocation pattern of energy and mechanical characteristics. Four characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 3 publications
1
8
0
Order By: Relevance
“…They concluded that rock’s internal structure and axial loading stress were the main factors affecting energy storage. Based on the principle of energy evolution and the hysteresis effect of concrete, Pei et al [ 31 ] conducted triaxial cyclic loading and unloading tests to study the influence of confining pressure on the energy storage limit, energy storage ratio, and energy consumption ratio. Through analysis of the energy evolution characteristics of the hysteresis loop of the stress-strain curve.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that rock’s internal structure and axial loading stress were the main factors affecting energy storage. Based on the principle of energy evolution and the hysteresis effect of concrete, Pei et al [ 31 ] conducted triaxial cyclic loading and unloading tests to study the influence of confining pressure on the energy storage limit, energy storage ratio, and energy consumption ratio. Through analysis of the energy evolution characteristics of the hysteresis loop of the stress-strain curve.…”
Section: Introductionmentioning
confidence: 99%
“…Many engineering projects have shown that rock is not in a stable stress environment but is subjected to a cyclic loading-unloading stress environment [9][10][11]. Tiered cyclic loading is a common form acting on rock mass, such as periodical change of the reservoir level and reciprocating motion of the train [12][13][14][15]. e rough fluctuation of rock fractures is suffered from periodic wear and passivation, leading to the deterioration of its shear strength under cyclic shear loading.…”
Section: Introductionmentioning
confidence: 99%
“…e essence of deformation and failure of rock mass is the instability driven by energy [15,23,24]. e energy evolution process involves energy absorption, agglomeration, dissipation, release, transformation and transmission [1].…”
Section: Introductionmentioning
confidence: 99%
“…ey analyzed and summarized the evolution law of cyclic acoustic emission of stress-strain changes of different rocks in loading and unloading stages. Pei and Yang et al [22,23] carried out triaxial cyclic loading and unloading tests of granite and deep-buried marble specimens under different confining pressures, respectively. e results show that the modulus of elasticity decreases with the loading and unloading cycles, while Poisson's ratio increases linearly.…”
Section: Introductionmentioning
confidence: 99%